Bulk synthesis of homogeneous and transparent bulk core/multishell quantum dots/PMMA nanocomposites with bright luminescence. Issue 3 (30th April 2013) - Ma, Yongsheng; Zhang, Bingbo; Gu, Mu; Huang, Shiming; Liu, Xiaolin; Liu, Bo; Ni, Chen
ABSTRACT Core/multishell CdSe/CdS/CdS/Cd0.75Zn0.25S/Cd0.5Zn0.5S/Cd0.25 Zn0.75S/ZnS/ZnS QDs/PMMA bulk nanocomposites were successfully synthesized. To achieve a homogeneous and stable dispersion in MMA monomers, QDs were first modified with amphiphilic polymer of poly(ethylene glycol)‐oleate (PEG‐oleate). Subsequently, the transparent and homogeneous bulk composites were obtained by photopolymerization. The TEM analysis of ultramicrotome cut of composite demonstrates that QDs are well dispersed in the PMMA matrix. UV–vis transmission spectra show the nanocomposites still maintain high transmittance even with QDs content of up to 6 wt %. The thermogravimetric analysis (TGA) reveals the incorporation of the QDs significantly improves the thermal stability of composites, as evidenced by the retardation of a degradation initiation by 60°C. Photoluminescence spectra suggest that the nanocomposites exhibit bright fluorescence under UV excitation. X‐ray excited luminescence spectra show they have response to X‐ray. All of the experimental results indicate the great promising applications of core/multishell QDs/PMMA nanocomposites in optical communication devices and radiation detectors. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 1548–1553, 2013